Prevalence and antibiogram profile of Mycobacterium spp. in poultry and its environments (Journal of Advanced Veterinary and Animal Research, 2015)
In this study, an attempt was undertaken to know the prevalence and antibiogram profile of Mycobacterium spp.  in  poultry  and  its  immediate  environments.  A total of 130 samples comprising of droppings (n=80), egg  washing  (n=18),  drinking  water  (n=14),  hand washing  from  farm  workers  (n=6)  and  litter  (n=12) were collected from six poultry farms located in and around  Bangladesh  Agricultural  University  (BAU). Samples  were  inoculated  onto  7H10  Middlebrook agar and incubated aerobically at 37ºC for 7-14 days. Identification of  Mycobacterium spp. was performed by  colonial  morphology,  acid  fast  staining,  and biochemical  tests.  Molecular  identification  of Mycobacterium spp. at genus level was performed by polymerase  chain  reaction  (PCR)  assay  targeting  65-kDa heat shock protein gene. Antibiogram profile of Mycobacterium  spp.  was  performed  against  five antibiotics  namely  Rifampin,  Azithromycin, Ciprofloxacin, Streptomycin and Doxycycline by disc diffusion  method.  Three  Mycobacterium  spp.  were isolated  from  dropping  samples  of  poultry.  The overall  prevalence  of  Mycobacterium  spp.  was  2.3% (n=3/130). All the isolates were resistant to Rifampin and  sensitive  to  Azithromycin  and  Ciprofloxacin. Data of this study indicated that multidrug resistant Mycobacterium  spp.  are  prevalent  in  the  poultry farms of the study area which underscore the need of implementation  of  good  biosecurity  to  poultry husbandry  practice  to  ensure  poultry  and  human health.http://dx.doi.org/10.5455/javar.2015.b118